Novel variants in helicase for meiosis 1 lead to male infertility due to non-obstructive azoospermia - Dongdong Tang; Mingrong Lv; Yang Gao; Huiru Cheng; Kuokuo Li; Chuan Xu; Hao Geng; Guanjian Li; Qunshan Shen; Chao Wang; Xiaojin He; Yunxia Cao (BMC, 2021)
Abstract Background Non-obstructive azoospermia (NOA) is the most severe form of male infertility; more than half of the NOA patients are idiopathic. Although many NOA risk genes have been detected, the genetic factors for NOA in majority of the patients are unknown. In addition, it is difficult to retrieve sperm from these patients despite using the microsurgical testicular sperm extraction (microTESE) method. Therefore, we conducted this genetic study to identify the potential genetic factors responsible for NOA and investigate the sperm retrieval rate of microTESE for genetically deficient NOA patients. Methods Semen analyses, sex hormone testing, and testicular biopsy were performed to categorize the patients with NOA. The chromosome karyotypes and Y chromosome microdeletion analyses were used to exclude general genetic factors. Whole exome sequencing and Sanger sequencing were performed to identify potential genetic variants in 51 patients with NOA. Hematoxylin and eosin staining (H&E) and anti-phosphorylated H2AX were used to assess the histopathology of spermatogenesis. Quantitative real time-polymerase chain reaction, western blotting, and immunofluorescence were performed to verify the effects of gene variation on expression. Results We performed whole exome sequencing in 51 NOA patients and identified homozygous helicase for meiosis 1(HFM1) variants (NM_001017975: c.3490C > T: p.Q1164X; c.3470G > A: p.C1157Y) in two patients (3.9%, 2/51). Histopathology of the testis showed that spermatogenesis was completely blocked at metaphase in these two patients carrying the HFM1 homozygous variants. In comparison with unaffected controls, we found a significant reduction in the levels of HFM1 mRNA and protein expression in the testicular tissues from these two patients. The patients were also subjected to microTESE treatment, but the sperms could not be retrieved. Conclusions This study identified novel homozygous variants of HFM1 that are responsible for spermatogenic failure and NOA, and microTESE did not aid in retrieving sperms from these patients.